Patient Identification in the Hemodialysis Unit Using the Plan-Do-Study-Act Approach - Dinda Iryawati Bedy Saskito; Kemal N. Siregar; Muhammad Fachri; STR Tri Handayani; Budi Hartono (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
This study determines the cause and solutions of the patient identification achievement that is not yet 100%, as the base to improve the patient identification system in the HD unit of GPI Hospital. Qualitative research using the Plan-Do-Study-Act (PDSA) approach involving triangulation of data collection, namely observation, documentation, and interviews with the PDSA NHS Improvement instrument. Informants were selected by snowball sampling. The PDSA results indicated that the problem cause was the HD team's lack of understanding of patient identification. This problem can be overcome by socialization and simulation of patient identification: a standard operating procedure for patient identification, implementation of patient identification, patient identification incident reporting flow, and money for patient identification. The problem of identifying patients in the HD unit can be resolved using the PDSA cycle that has been performed. Modifications are required for the next PDSA cycle, consisting of 1) regular socialization and simulation of patient identification; 2) SOP of patient identification in HD unit; 3) implementation of the identification process by involving the patient; 4) reporting and building awareness of realizing a patient safety culture if an incident occurs, and 5) reporting on the achievement of monev data and recommendations for improvement efforts.